Effect of the age of broodstock males on sperm function during cold storage in the trout (Oncorhynchus mykiss). (21st July 2017) - Risopatrón, J.; Merino, O.; Cheuquemán, C.; Figueroa, E.; Sánchez, R.; Farías, J. G.; Valdebenito, I.
Summary: The knowledge of sperm quality in the broodstock males of different ages is a prerequisite to identify the reproductive ability of cultivated fish for the hatchery management. Thus, in this work, we analysed sperm function of the semen stored of broodstock males of rainbow trout ( Oncorhychus mykiss ) in different reproductive ages (2, 3 and 4 years old). Sperm samples of each reproductive age were stored in Storfish ® during 10 days at 4°C, and then, motility, viability, mitochondrial function (MMP), superoxide anion ( O 2 − ) level and DNA fragmentation (DNAfrag ) were assessed. The results demonstrated that sperm function parameters were affected significantly by the age of the males and the time of storage. Motility, viability and MMP significantly decreased, and DNAfrag and O 2 − level increased with the age increment and the time of storage. In conclusion, sperm quality of 2 and 3 years old were superior to those of 4 years old, based on higher quality of various sperm functions such as motility, viability, MMP, DNA integrity and level O 2 − during short‐term storage. This information must be considered for optimum utilization of broodstock males in aquaculture.